Self-assembly of poly(ionic liquid) (PIL)-based amphiphilic homopolymers into vesicles and supramolecular structures with dyes and silver nanoparticles. Issue 22 (16th May 2017) - Manojkumar, Kasina; Mecerreyes, David; Taton, Daniel; Gnanou, Yves; Vijayakrishna, Kari
Abstract : Self assembly of amphiphilic homo-PILs. Abstract : The incorporation of both hydrophilic and hydrophobic segments in homopolymers leads to their self-assembly into nanostructures in selective solvents, owing to their amphiphilic character. Here we report the RAFT polymerization of N -imidazole-3-propylmethacrylamide and the further quaternization of the resulting polymer with different alkyl bromides of a varying chain length, which afforded well-defined polymeric ionic liquids (PILs)1–4 . These PILs are characterized by the presence of both hydrophobic alkyl chains and hydrophilic ionic moieties, allowing their spontaneous self-assembly in water, forming distinct polymeric vesicles (= polymersomes) the size of which can be varied as a function of alkyl chain length. As demonstrated by the dye-encapsulation study, a particular organic-soluble PIL, 3, consisting of a dodecyl side-chain enabled the transfer of the water-soluble Rose Bengal dye, from an aqueous solution to the organic phase. In addition, polymersomes obtained from a PIL (2 ) featuring butyl side chains were used as templates and polymeric stabilizers of silver nanoparticles (NPs), i.e. leading to AgNP@PIL hybrids, as observed by transmission electron microscopy (TEM). It was found that the extent of functionalization of polymersomes by the Ag-based NPs varied greatly before and after the end-group removal of the PIL. Altogether, this report emphasizes the facile synthesis of amphiphilic homoPILs and their manipulation in water for dye encapsulation and for stabilization of silver NPs.